Influence of defocus distance on laser joining of CFRP to titanium alloy. (April 2020) - Su, Jianhui; Tan, Caiwang; Wu, Zhuolun; Wu, Laijun; Gong, Xiangtao; Chen, Bo; Song, Xiaoguo; Feng, Jicai
Highlights: Defocus distance affected the adhesion width of the resin significantly. The strength of TC4/CFRP-PEEK joint depended on the adhesion width of the resin. CTi0.42V1.58 phase was identified at the joining interface. Defects on the surface of TC4 gradually increased with the increase of defocus distance. Abstract: Laser joining of carbon fiber reinforced polyether ether ketone (CFRP-PEEK) to titanium alloy (TC4) was performed. The influence of defocus distance, also described as irradiance diameter of laser beam on interfacial joining was investigated. The appearance of welded joint and the microstructure at joint interface was observed. The fracture load was thereafter obtained. In addition, temperature field simulation at the joint interface during laser joining process was carried out to clarify the joining mechanism. The results indicated that good appearances were obtained with low defocused distance. The interfacial observation showed that mechanical bonding was generated at the joint interface since the melted resin was embedded in the rough surface of the TC4. Besides, a new phase formed at the interface between CFRP-PEEK and TC4, which was identified as CTi0.42 V1.58 . The content of the phase increased as the defocus distance increased. Shear force decreased when the defocus distance increased from −4 mm (irradiance diameter 0.84 mm) to 0 mm (irradiance diameter 0.6 mm), and then increased when the defocus distance increased from 0 mm to +8 mm (irradiance diameter 1.06 mm). This phenomenon was explained by simulation result of temperature field that the width of the range of melting temperature of the resin increased as the laser beam diameter increased. The simulation results were consistent with the changes of the width of resin adhesion in actual joint.